Sociodemographic, Household, and Environmental Determinants of Recent Diarrhea Among Under-Five Children in Indonesia: Evidence from the 2017 IDHS - Risiska Rahayu Safitri; Musthika Wida Mashitah; Yuni Asri (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Background: Diarrhea remains a health problem in Indonesia. Despite various prevention programs, the prevalence of diarrhea in children in Indonesia remains relatively high. Objective: This study aimed to analyze factors associated with recent diarrhea among children under five years of age in Indonesia. Methods: This study used a cross-sectional design based on secondary data from the 2017 Indonesian Demographic and Public Health Survey (PJS). A total of 13,756 weighted mother-child pairs were included in the analysis. Sampling weights were applied prior to statistical analysis to account for the complex survey design. Data were analyzed using the chi-square test and binary logistic regression analysis was performed to identify factors associated with recent diarrhea. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were reported. Results: The prevalence of recent diarrhea in children under five years of age was 14.9%. Maternal age, maternal education, husband/partner's education level, province, household wealth index, and child gender were significantly associated with diarrhea incidence. Children from poor households were more likely to experience diarrhea compared to children from wealthier households. Boys were more likely to experience diarrhea than girls (AOR=1.19; 95% CI=1.08–1.31). Regional differences were also observed, particularly among children living outside Java–Bali. Conclusion: Strengthening maternal education, improving household socioeconomic conditions, and reducing regional differences are crucial to support childhood diarrhea prevention programs in Indonesia.